PENGARUH TINGKAT SUKU BUNGA (SBI) DAN INFLASI TERHADAP IHSG INDUSTRI PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) - Yuliawan Yuliawan (Institut Ilmu Sosial dan Manajemen STIAMI, 2016)
The capital market has a strategic role to strengthen the economic resilience of a country and as a favorable alternative investment destination. Capital markets have an important role to the economy of a country because the capital market runs two functions, namely economic function and financial function. The capital market becomes a driver of the national economy through its role as a source of corporate financing and an alternative for investors to invest. In the capital market, the Composite Stock Price Index (CSPI) plays an important role, because this index can be a barometer of economic health in a country. Macroeconomic factors such as high inflation, interest rates and depreciation of the rupiah against the dollar will lower stock prices. This study aims to examine the effect of macroeconomic factors such as inflation and interest rates on the composite stock price index (IHSG) in Indonesia Stock Exchange (IDX).The analysis method using multiple linear regression analysis model. The data used in this study is the monthly secondary data period 2013-2016. This study used 36 samples. The structural equation for this multiple linear regression analysis is Y = -382,192 X1 + 278,977 X2.The inflation and interest rate / BI Rate variable can explain the JCI in this multiple linear regression analysis model of 4.9%. The correlation between variable inflation and interest rate / BI Rate to JCI of 0.322 is quite strong. From the calculation, F arithmetic <F table (1.907 <8.92), it can be concluded there is no linear relationship between inflation, interest rate / BI Rate and exchange rate against JCI.